Vegetation Dynamics, Changing Ecosystems and Human Responsibility - Hufnagel, Levente; El-Esawi, Mohamed A. (Environmental Sciences, 2023)
Vegetation Dynamics, Changing Ecosystems and Human Responsibility provides an overview of vegetation dynamics, which is the science of natural, near-natural, and human-influenced changes in vegetation over time and space. We can find chapters about almost every viewpoint of this very diverse segment of our science and in connection with almost every main type of terrestrial ecosystem.